2012
DOI: 10.1364/oe.20.016129
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in spectral behavior of total losses (1 − R − T) in thin dielectric films

Abstract: Abstract:We explain reasons of oscillations frequently observed in total losses spectra (1 − R − T ) calculated on the basis of measurement spectral photometric data of thin film samples. The first reason of oscillations is related to difference in angles of incidence at which spectral transmittance and reflectance are measured. The second reason is an absorption in a thin film. The third reason is a slight thickness non-uniformity of the film. We observe a good agreement between theoretical models and corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…These reflected waves interfere with each other and lead to the observed interferences in light transmission. [47][48][49][50] As expected, the PaC/sAu had no detectable light transmittance across all wavelengths and PaC/PP showed consistently high transmittance. In comparison with the opaque metal, PaC alone exhibits strong absorption of UV light until 280 nm followed by a rapid increase reaching a mean of 80% transmittance at 352 nm.…”
Section: Electrical and Electrochemical Performance Of Lecogssupporting
confidence: 74%
See 1 more Smart Citation
“…These reflected waves interfere with each other and lead to the observed interferences in light transmission. [47][48][49][50] As expected, the PaC/sAu had no detectable light transmittance across all wavelengths and PaC/PP showed consistently high transmittance. In comparison with the opaque metal, PaC alone exhibits strong absorption of UV light until 280 nm followed by a rapid increase reaching a mean of 80% transmittance at 352 nm.…”
Section: Electrical and Electrochemical Performance Of Lecogssupporting
confidence: 74%
“…These reflected waves interfere with each other and lead to the observed interferences in light transmission. 47–50…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [ 18 ] reported similar observations on the decreasing transmittance of gas barrier films based on the increasing thickness of the films. The oscillations observed in the transmittance results are due to the waveguide of the thin film, which is dependent on the thickness of the films [ 21 ]. In contrast, the decreasing light transmittance within the visible range of the bilayers can be attributed to the thickness of the films.…”
Section: Resultsmentioning
confidence: 99%
“…The reflectance R and transmittance T spectra were measured using a spectrophotometer device (Lambda 950, PerkinElmer Inc., Waltham, MA, USA) from 190 to 1200 nm wavelength within a measurement accuracy of ±0.3%. The optical losses (OL) are calculated using the following expression [64][65][66]: OL = 1-T-R.…”
Section: Characterizations Of the Sio 2 :Hfo 2 Heterostructure Filmsmentioning
confidence: 99%